2014
DOI: 10.1159/000366002
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Chronic Pain: Diffusion Tensor Imaging Identification of the Ventroposterolateral Nucleus Confirmed with Successful Deep Brain Stimulation

Abstract: Background/Aims: A variety of pain syndromes have been treated successfully with deep brain stimulation (DBS) by targeting the thalamic ventroposterolateral (VPL) nucleus. The purpose of this study was to preoperatively identify the thalamic VPL nucleus by diffusion tensor imaging (DTI) fiber tractography (FT) and confirm it intraoperatively. Methods and Results: FT was performed to identify the thalamic VPL nucleus in 6 healthy volunteers and a patient with intractable chronic pain. The patient had preoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 29 publications
(61 reference statements)
0
12
0
Order By: Relevance
“…Studies in non-human primates have shown that the thalamic ventrobasal complex (the caudal division of the VPL nucleus and the large-celled portion of the ventroposteromedial nucleus) project to primary and secondary somatosensory areas (S1 and S2) [2331]. In humans, the ventroposterior nuclei (VPL and VPM) have the strongest probability of primary somatosensory cortical connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in non-human primates have shown that the thalamic ventrobasal complex (the caudal division of the VPL nucleus and the large-celled portion of the ventroposteromedial nucleus) project to primary and secondary somatosensory areas (S1 and S2) [2331]. In humans, the ventroposterior nuclei (VPL and VPM) have the strongest probability of primary somatosensory cortical connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Current theory broadly postulates that DBS modulates fiber pathways in the pain network in order to treat chronic pain, although the exact mechanism is not understood [2,21,43,44,45,46]. DBS of the nucleus accumbens (NAcc) in control rats prompted a decreased metabolism in the basal ganglia and periaqueductal gray, while metabolism increased in the subiculum [47].…”
Section: Methodsmentioning
confidence: 99%
“…It is currently believed to constitute components of the lateral pain system, and as such the area became a major target of interest in the earliest studies of DBS for DRS [38,43,44,45]. Contemporary practice is to specifically target the VPM for facial pain, while the VPL can be a target for arm and leg pain [45].…”
Section: Methodsmentioning
confidence: 99%
“…Case studies characterizing optimal DBS targets using DTI have isolated specific relevant white‐matter targets [Anthofer et al, ; Kovanlikaya et al, ; Riva‐Posse et al, ; Schlaier et al, ; Sweet et al, ]. However, these studies have been limited to small sample sizes, and tractography measures have been based on deterministic rather than probabilistic tractography, whereas the latter has been demonstrated to provide more robust estimates of underlying white‐matter structures [Descoteaux et al, ].…”
Section: Introductionmentioning
confidence: 99%